Mechanism of increased efficacy of recombinant Fc‐μTP‐L309C compared to IVIg to ameliorate mouse immune thrombocytopenia. Issue 4 (29th September 2021) - Lewis, Bonnie J.B.; Binnington, Beth; Blacquiere, Megan; Spirig, Rolf; Käsermann, Fabian; Branch, Donald R.
Abstract: Recombinant Fc‐μTP‐L309C is more efficacious than intravenous immunoglobulin (IVIg) at ameliorating antibody‐mediated autoimmune diseases through its effects on Fcγ receptors (FcγRs). Fc‐μTP‐L309C inhibited in‐vitro FcγR‐mediated phagocytosis 10 4 /10 5 ‐fold better than IVIg. Fc‐μTP‐L309C, given subcutaneously, recovered platelet counts in an immune thrombocytopenia (ITP) mouse model to a higher degree than IVIg at a 10‐fold lower dose. We show, using confocal microscopy, that Fc‐μTP‐L309C binds to monocyte‐macrophages and is rapidly internalized, whereas, IVIg remains on the cell surface. Western blotting showed that internalized FcγRIII is degraded through a lysosomal pathway, and this reduction of cell surface FcγRIII is likely responsible for the increased efficacy to ameliorate ITP.